Bilateral Pulmonary Arteriovenous Malformation in Female Patient Based on Computed Tomography Imaging: A Rare Case Report - Sutrisno, Sony (Indonesian Journal of Medicine, 2021)
Background: Pulmonary arteriovenous malformations (PAVMs) is an extremely rare vascular anomaly due to a direct connection between the pulmonary artery and pulmonary vein, potentially causing irreversible damages to the systemic circulation. This condition requires a prompt diagnostic approach to ensure early diagnosis and treatment.Case Report: A 53-year-old Indonesian female was referred to our department with unexplained dyspnoea and cyanosis. Physical examination revealed low oxygen saturation and remarkable finding on pulmonary auscultation. Further investigation revealed the findings suggesting PAVM based on contrast-enhanced chest computed tomography (CT) scan, with multiple nidus on bilateral lungs with feeder arteries from the pulmonary artery and draining veins in the pulmonary vein. Hence, this case emphasizes the rare finding of a female PAVMs patient with bilateral PAVMs.Conclusion: CT scan is a reliable and effective imaging approach to establish the diagnosis of PAVMs. This modality should be first considered to visualize PAVMs lesions, particularly in adult patients with unexplained dyspnoea and cyanosis.Keywords: arteriovenous malformations, CT scan, rare case, embolizationCorrespondence: Sony Sutrisno. Department of Radiology, Faculty of Medicine and Health Sciences, Krida Wacana Christian University, Jakarta, Indonesia. Email: sonysutrisnodr@gmail.com. Mobile: +62-8128-9290-414. Indonesian Journal of Medicine (2021), 06(04): 393-398https://doi.org/10.26911/theijmed.2021.06.04.05